(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2021)
The Surma River is one of the most important rivers in the northeastern part of Bangladesh, which has changed significantly throughout history. Very few studies have taken place to understand this river’s complex behavior, which characterizes its morphology. The core objective of this research is to analyze the river dynamics to understand the morphological changes of the river from 1978 to 2021. Remotely sensed satellite images of 1978, 1989, 1999, 2011, and 2021 were secondary data. The whole working procedure is the correction of satellite images, application of normalized difference water index (NDWI), demarcation of the river bank line using bank line methods, quantification of the erosion-deposition using an overlapping method, demarcation of central line shifting, measurement of the river width and finally the sinuosity index metering for 43 years. The river has changed significantly in several locations within the period in Sylhet District. Ten bends, three segments, and 200 points were taken to quantify the change dynamics. The overall analysis found that the left bank shifted more than the right bank. According to the findings, the deposition rate (80.98m/year) of river Surma is almost double the erosion rate (42.11m/year), which causes a significant decline in river width from 163m in 1978 to 123m in 2011. After counting 200 sample points, the result concluded that the average central line shifted more than average (79.50m) at 38 points indicates three major locations- Kanaighat, Dakshin Banigram, and Lalargaon. Finally, the sinuosity index found that the river became more meander following its shifting movement except the ninth bend near Kandigaon. The riverine people indicated several anthropogenic factors, e.g., encroachment, illegal construction, pollution, illegal sand extraction, as the key issues which should be intervened and take necessary action. Â